The economics of higher education - Holmes, C; Mayhew, K (Oxford University Press, 2016)
This paper describes the expansion of higher education (HE) in OECD countries and discusses its economic consequences. For most governments this expansion has been seen as the silver bullet that improves economic growth and helps tackle problems of inequality. However, in most countries increasing numbers of graduates are going into jobs that were once done by non-graduates, raising the concern that the true social returns to HE expansion are low. Because of this it is unsurprising that economists have found it difficult to establish firm links between higher education expansion and economic growth. At the same time, in some countries, HE expansion has exacerbated problems of economic and social inequality. The paper argues that governments need to take a more realistic view of the role of HE, consider alternative ways of preparing people for the labour market, and at the same time explore more rigorously exactly how the sector is conducting itself.